2019
DOI: 10.1111/geb.12981
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analyses of multi‐trophic terrestrial vertebrate assemblages in Europe

Abstract: Aim Although much has been said on the spatial distribution of taxonomic and phylogenetic diversity of vertebrates, how this diversity interacts in food webs and how these interactions change across space are largely unknown. Here, we analysed the spatial distribution of tetrapod food webs and asked whether the variation in local food web structure is driven by random processes or by natural and anthropogenic factors. Location Europe. Time period Present. Major taxa studied Tetrapods. Methods We combined an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(81 citation statements)
references
References 79 publications
3
76
2
Order By: Relevance
“…For each species, we gathered information on species‐specific trophic links plus a set of 11 trophic items: mushrooms, mosses/lichens, algae, detritus, seeds–nuts–grains, fruits, other plant parts, invertebrates, fish, domestic animals and faeces. These diet items could then be used as basal food items in the network (see Braga et al, 2019; O’Connor et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For each species, we gathered information on species‐specific trophic links plus a set of 11 trophic items: mushrooms, mosses/lichens, algae, detritus, seeds–nuts–grains, fruits, other plant parts, invertebrates, fish, domestic animals and faeces. These diet items could then be used as basal food items in the network (see Braga et al, 2019; O’Connor et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…This could yield false negatives in our dataset (i.e., interactions that exist in nature but that we characterized as non-existent because the literature fails to document those interactions). Using the approach proposed by Morales-Castilla et al (2015), it is possible to use data on species' ecology (e.g., habitat preferences) and distribution (for example considering the data presented in Maiorano et al 2013) to distinguish potential trophic links (what we reported) from trophic links actually occurring (see Braga et al 2019 andO'Connor et al 2020).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because we almost can, and because we definitely should. A better understanding of species interactions, and the networks they form, would help unify the fields of community, network, and spatial ecology; improve the quantification of the functional relationships between species (Dehling and Stouffer 2018;O'Connor et al 2020); re-evaluate metacommunities in light of network structure (Guzman et al 2019); and enable a new line of research into the biogeography of species interactions (Massol et al 2017;Braga et al 2019) which incorporates a synthesis of both Eltonian and Grinnellian niche (Gravel et al 2019). Further, the ability to reliably predict and forecast species interactions would inform conservation efforts for protecting species, communities, and ecosystems.…”
Section: Conclusion: Why Should We Predict Species Interaction Network?mentioning
confidence: 99%
“…Thus, understanding their behavioural modulation can greatly help unravel predator-prey interaction mechanisms. Even though being a meso-or an apex predator is generally related to body size, with larger predators preying upon smaller ones (Eklov and Svanback 2006;Donadio and Buskirk 2016), the position of a species within food webs is strongly context dependent and may differ between habitats and ontogenic stage (Ritchie and Johnson 2009;Braga et al 2019). In streams without fish, dragonfly larvae are a classical example; at early life-stages, these organisms occupy an intermediate position in the food webs while, once they grow, they become the apex predators (Hopkins et al 2011;Start 2018).…”
Section: Introductionmentioning
confidence: 99%